Penerapan Pembagian Waris Beda Agama Pada Etnis Tionghoa Di Kabupaten Bungo Provinsi Jambi - Dianis, Ratna; Azheri, Busyra; Hasbi, Muhammad (Nagari Law Review, 2024)
The Chinese ethnic group is one of many ethnicities or tribes that contain communities with quite complex religious plurality, within the Chinese ethnic group there are people who are Muslim, Buddhist, Hindu, Christian and also Confucian. The diversity of religions in the ethnic Chinese traditional community also gives rise to several legal options that can be chosen to be applied, especially in matters of inheritance, where there are at least 3 (three) inheritance law provisions that can be used, namely civil inheritance law, customary inheritance law, and also inheritance law of Islam. The differences in religion adhered to between heirs and heirs will raise several questions related to this regarding: 1. How implementation of inheritance from different religions in the ethnic Chinese community in Bungo Regency? 2. What is the influence of the legal system in terms of regulating and implementing inheritance of different religions by ethnic Chinese in Bungo Regency? 3. What are the legal steps for a Notary if a client visits him who wants to arrange an inheritance deed but the parties to the deed have different religions? The research method used is an empirical juridical method. This research is descriptive. Data collection techniques are document study and interviews. From the research results, in general, the Bungo Chinese ethnic community chooses a very different inheritance rules, there are some people choose to use Chinese inherintance rules, the others choose to use the inheritance rules of the Civil Code, Apart from the two inheritance rules above, a small percentage of people choose to implement Islamic inheritance rules, and there are also who choose rules of inheritance base on agreement.